Analisis Sub Sektor Unggulan di Kabupaten Pemalang Tahun 2001-2010 - Yunie Mastuti Handayani (EKO-REGIONAL, 2012)
This research is to analyze the advantage of subsectors in Pemalang Regency. The method of this research is Klassen Typology and Location Quotient (LQ) using secondary data, 2001-2010, from Badan Pusat Statistik (BPS) of Central Java Province and Pemalang Regency, and Dinas Pendapatan, Pengelolaan Keuangan, and Aset Daerah (DPPKAD) of Pemalang Regency. The result shows that based on Klassen Typology the subsector which has significant progress and grows rapidly is fishery and based on LQ the basic subsectors are plants for food, plantation, animal husbandry, fishery, mining, electricity, restaurant, building rent, firm service, and private subsector. The conclusion of both analysis shows that fishery is the most advantage subsector in Pemalang.   Keywords: klassen typology, location quotient, fishery, basic sub-sector